2009
DOI: 10.1074/jbc.m109.057729
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting Protein (Txnip) Is a Feedback Regulator of S-Nitrosylation

Abstract: Nitric oxide exerts a plethora of biological effects via protein S-nitrosylation, a redox-based reaction that converts a protein Cys thiol to a S-nitrosothiol. However, although the regulation of protein S-nitrosylation has been the subject of extensive study, much less is known about the systems governing protein denitrosylation. Most recently, thioredoxin/thioredoxin reductases were shown to mediate both basal and stimulus-coupled protein denitrosylation. We now demonstrate that protein denitrosylation by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 59 publications
2
73
1
Order By: Relevance
“…S-nitrosation and denitrosation of cellular proteins are regulated through an enzymatic complex, in which thioredoxins, thioredoxin reductase, thioredoxin-interacting protein, and Snitrosoglutathione reductase orchestrate the cellular pool of SNOs and, therefore, protein function (24,41). In addition, the fact that S-nitrosation of a given protein depends on its subcellular localization, rather than solely on the amount of available NO, further emphasizes that S-nitrosation is a finely controlled mechanism (17,29,41), an imbalance of which is linked to genesis of several pathologic states (13, 16-18, 41). We conjecture that, during the response to cisplatin, a process is activated in which NO concentration increases and SNO levels are modulated by the aforementioned enzymes (together with other mechanisms yet to be identified), enabling cancer cells to mitigate apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…S-nitrosation and denitrosation of cellular proteins are regulated through an enzymatic complex, in which thioredoxins, thioredoxin reductase, thioredoxin-interacting protein, and Snitrosoglutathione reductase orchestrate the cellular pool of SNOs and, therefore, protein function (24,41). In addition, the fact that S-nitrosation of a given protein depends on its subcellular localization, rather than solely on the amount of available NO, further emphasizes that S-nitrosation is a finely controlled mechanism (17,29,41), an imbalance of which is linked to genesis of several pathologic states (13, 16-18, 41). We conjecture that, during the response to cisplatin, a process is activated in which NO concentration increases and SNO levels are modulated by the aforementioned enzymes (together with other mechanisms yet to be identified), enabling cancer cells to mitigate apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Trx2 was identified as a denitrosylase of mitochondrial caspase-3 upon Fas ligand stimulation, a process required for its activation and, therefore, for apoptotic cell death (16). Furthermore, the Trx-interacting protein (Txnip) has been shown to inhibit denitrosylate activity of Trx, since it increases SNOprotein levels (43).…”
Section: Denitrosylasesmentioning
confidence: 99%
“…In addition, NO cGMP independently represses the transcription of thioredoxin-interacting protein (TXNIP), which not only enables antioxidative actions of thioredoxins, but also stimulates thioredoxin-dependent protein denitrosylation, thus providing a negative feedback mechanism protecting against excessive protein S -nitrosylation and nitrosative stress [10]. Shaked et al [11] demonstrated that the NO-dependent TXNIP inhibition contributed to the protective effect of insulin against glucose-induced beta cell apoptosis.…”
Section: Admamentioning
confidence: 99%